Problems and Factors of Non-Completion of Promising Projects by Young Entrepreneurs: The Case of Tunisia - Hamed, Salah Ben (Information Management and Business Review, 2014)
Our study attempted to explore the different problems and factors of the non-completion of business projects by a representative sample of project promoters. Four factors were selected to examine the issue, which are: resources availability and ease of access to finance, lack of capital and its impact on projects, promoters’ competencies and cognitive skills and their projects vision as entrepreneurs to overcome obstacles. A Principal Component Analysis (PCA) has shown that the financial factor is the main factor of the non-completion of promising projects by young project promoters.